Pneumatosis cystoides intestinalis in dermatomyositis: a case series report and literature review - Liu, Jianwen; Zhang, Ling; Chen, Shuo; Lu, Xin; Li, Shanshan (Frontiers in Immunology, 2023)
Pneumatosis cystoides intestinalis (PCI) in adult dermatomyositis(DM) is rarely described. We describe the clinical features and prognosis of PCI in 6 adult DM patients(4 with anti-MDA5 antibody, 1 with anti-SAE antibody and 1 with anti-TIF-1r antibody). Except for 1 patient with transient abdominal pain, the remaining five patients were asymptomatic. PCI occurred in the ascending colon in all patients, where 5 had free gas in the abdominal cavity. All of the patients did not receive excessive treatment, and PCI disappeared in 3 patients during the follow-up. In addition, we reviewed previous literature concerning on this complication.